2020
DOI: 10.1007/s11252-020-00940-4
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of semi-natural cover with artificial substrates in urban parks causes a decline of house sparrows Passer domesticus in Mediterranean towns

Abstract: Many European towns and cities have undergone reurbanisation processes in recent decades. However, their effects on urban biodiversity have been poorly studied. Currently urbanisation processes include park remodelling, which involves the replacement of semi-natural substrates (natural grass, bare soil) with artificial ones (pavement, concrete, areas for dogs, artificial grass). Our aim was to explore, for the first time, the effects of park remodelling on the trends and abundance of a declining urban exploite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…Recently, urban management has relied on a 'renaturing of cities' strategy to improve biodiversity, but the relative benefits of alternative policies remain debated (Connop et al 2016;Garmendia et al 2016;Snäll et al 2016). Specifically, it has been suggested that all green spaces do not have similar value in terms of habitat suitability, and that highly fragmented, small, and isolated green spaces may be of limited ecological value relative to larger and more connected green spaces (Beninde et al 2015;Bernat-Ponce et al 2020;Lepczyk et al 2017;Villaseñor et al 2020). In the last decade, the development of connected green infrastructures and ecological corridors has been proposed as a way to improve the colonization of wildlife and, therefore, urban biodiversity (Filazzola et al 2019;Vergnes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, urban management has relied on a 'renaturing of cities' strategy to improve biodiversity, but the relative benefits of alternative policies remain debated (Connop et al 2016;Garmendia et al 2016;Snäll et al 2016). Specifically, it has been suggested that all green spaces do not have similar value in terms of habitat suitability, and that highly fragmented, small, and isolated green spaces may be of limited ecological value relative to larger and more connected green spaces (Beninde et al 2015;Bernat-Ponce et al 2020;Lepczyk et al 2017;Villaseñor et al 2020). In the last decade, the development of connected green infrastructures and ecological corridors has been proposed as a way to improve the colonization of wildlife and, therefore, urban biodiversity (Filazzola et al 2019;Vergnes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…First, design and management of green areas should promote weeds, bushes and native plants that harbour important food resources for House sparrows such as invertebrates and seeds (Bernat-Ponce et al 2018;Narango et al 2018). The substitution of grass and soil with impervious substrates such as artificial grass and concrete has been shown to affect negatively to House sparrows (Bernat-Ponce et al 2020;Verbeeck et al 2011), likely due to the reduction of food resources and thus should be avoided. Second, it is important to promote new urban green areas that work as green stepstones, including parks and private gardens, especially in areas with underground rubbish containers (De Laet and Trappeniers 2019;Shaw et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Urbanisation is increasing all over the world at surprisingly quick rates (Murgui and Hedblom 2017;United Nations 2018). This process affects wildlife in many ways, for example, modifying habitat structure which renders some landscapes unsuitable for several species (Bernat-Ponce et al 2020;Isaksson 2018;Murgui and Hedblom 2017;Verbeeck et al 2011). These modified environments pose a new challenge for urban avifauna through exposure to novel stressors, such as pollutants, noise, new predators, exotic competitors or processed food (Bernat-Ponce et al 2018;Francis and Barber 2013;Herrera-Dueñas et al 2017;Murgui and Hedblom 2017;Schroeder et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, van Manen [48] indicated that the House Sparrow has currently declined most heavily in highly urbanized areas in the Netherlands, and in Spain, the species decrease has been linked with the high-impact urban development [82]. In general, changes in land use practices and local habitat characteristics may influence the sparrow's occurrence and abundance [42,[83][84][85][86][87]. However, we are not able to study these topics in more detail, but obviously, there can be some differences between the sparrow's winter and breeding season habitat use that will serve further research.…”
Section: Sparrow Populations Growth Rates In Finlandmentioning
confidence: 99%